A groundwater–soil–plant–atmosphere continuum approach for modelling water stress, uptake, and hydraulic redistribution in phreatophytic vegetation. Issue 3 (21st August 2013) - Gou, Si; Miller, Gretchen
ABSTRACT Modelling groundwater uptake provides a powerful tool for examining the tight linkage of phreatophytic vegetation with spatial and temporal variations in groundwater and soil moisture. Here, a physically based modelling framework was developed to simulate groundwater uptake and hydraulic redistribution (HR), as driven by the potential gradients along the groundwater–soil–plant–atmosphere continuum. A new water stress function, based on the 'vulnerability curve' theory, was introduced; it integrates the influence of both soil water and groundwater on transpiration. The model was then implemented using a system dynamics approach and applied to simulate groundwater uptake of Quercus douglasii (blue oak) in a California savanna. It showed good agreement with the measured evapotranspiration, soil moisture, and leaf water potential data. The model results indicated that the dominant water source for blue oaks switched from soil water in the wet season to groundwater in the dry season. During the dry period, cavitation led to a hydraulic conductivity loss of approximately 85% in the shallow roots, and groundwater uptake contributed over 80% of transpiration. The dry, shallow soil layers received water from groundwater and deep soil layers at night through HR. The new water stress function performed well when simulating daily transpiration (r2 = 0·69). The model indicated that blue oaks maintained only a small portion of deep roots (15% of the total) to uptake groundwater and mitigate the impacts of drought. The proposed model framework can be incorporated into coupled climate, hydrological, and ecological models to improve their performance when studying ecohydrological process and climate feedbacks. Copyright © 2013 John Wiley & Sons, Ltd.